Bon appétit ! = Guten Appetit! - Rossellini, Isabella 1952-; Dzieweczynski, Artur (Arte, 2011)
Script: Isabella Rossellini denounces the dangers of excessive fish farming. [orange.com]
Fernsehmitschnitt: Arte 11.05.2011
Orig.: Frankreich 2010